PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. SOCFIN INDONESIA - rini astuti; Tina Fitria Tarigan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2020)
This study aims to determine the effect of work stress and work environment on employee performance at PT. Socfin Indonesia. The approach in this research is to use quantitative and associative approaches. The determination of the number of samples taken as respondents in this study were 68 employees. The data collection techniques in this study were interviews, documentation and a questionnaire, this positive value means that if stress and the work environment are increased, employee performance will increase. From the F test, it is obtained 0.451 with sig 0.000 <0.05, indicating that Ho is rejected and Ha is accepted, meaning that work stress (X1) and work environment (X2) have a significant effect on employee performance (Y) at the 0.05 level. The coefficient of determination obtained (R-Square) is 0.014 or 14%, indicating that about 14% of the Y variable can be explained by the work stress variable (X1) and the work environment (X2) or it can be practically said that the contribution of work stress (X1) and work environment (X2) on employee performance (Y) is 14%, the rest is influenced by other variables not examined.